Cardiac telerehabilitation with long-term follow-up reduces GlycA and improves lipoprotein particle profile: A randomised controlled trial. (15th December 2022) - Dalli-Peydró, Ernesto; Gisbert-Criado, Rafael; Amigó, Nuria; Sanz-Sevilla, Nuria; Cosín-Sales, Juan
Abstract: Background: A 10-month strategy of cardiac telerehabilitation (CTR) improved outcomes over a standard centre-based cardiac rehabilitation (CBCR), as recently published. We hypothesised that prolonged telerehabilitation could also improve proinflammatory status and lipoprotein particle composition. Methods: A randomised controlled trial compared a prolonged CTR program with CBCR in post-ACS patients. Patient's age was 18–72 years with low-risk criteria. Blood samples were drawn at baseline, at 4- and 10-months follow-up. Advanced lipoprotein characterization was performed using the NMR-based Liposcale test. Signals from glycoproteins (GlycA and GlycB) were also assessed. Results: The final analysis included 31 patients in the CTR group and 25 patients in the CBCR group . GlycA decreased in the CTR group ( p = 0, 007). LDL particle number (LDL-P) increase in both groups, but it was at the expense of small-sized LDL in the CBCR group ( p = 0.012). Triglycerides in intermediate-density lipoprotein (IDL-TG) increased only in the CBCR group ( p = 0.043). The triglyceride-to-HDL (TG/HDL) ratio decreased only in the CTR group ( p = 0.006). The TG/HDL ratio was correlated with GlycA (Spearman's correlation coefficient: 0.558, p < 0.001) but not with CRP ( p = 0.101). Conclusions: Our results showed that a 10-month CTR program reduced GlycA levels, the TG/HDL ratio and avoided unfavourable long-term changes in lipoprotein particle composition. Registration at http://ClinicalTrials.gov . NCT number: 04942977 Graphical abstract: Graphical abstract Unlabelled Image Highlights: GlycA levels are associated with risk of new coronary events and mortality. Small lipoprotein particles are associated with atherosclerosis progression. Extended cardiac telerehabilitation reduced GlycA levels. Extended cardiac telerehabilitation prevented unfavourable lipoprotein changes. These results could modify rehabilitation protocols if confirmed subsequently.